Synthesis and Electrochemical Property of FeOOH/Graphene Oxide Composites - Chen, Xingying; Zeng, Yanyang; Chen, Zehua; Wang, Shuo; Xin, Chengzhou; Wang, Lixia; Shi, Changliang; Lu, Liang; Zhang, Chuanxiang (Frontiers in Chemistry, 2020)
A facile ultrasonication method was used to uniformly mix nanospindle-shaped FeOOH (80-100 nm) and a conductive matrix of graphene oxide (GO) to form FeOOH/GO composites. No carbon peak was observed in the X-ray diffraction pattern, indicating that the graphene oxide did not stack together and that the dispersion of graphene was very high. X-ray photoelectron spectroscopy (XPS) tests showed that the formation of Fe-O-C bonds played a positive role in electron transport, revealing that it has a certain impact on the electrochemical performance of FeOOH/GO. The FeOOH/GO was further characterized by TGA, and the content of GO in the synthesized sample was 6.68%. Compared with that of FeOOH, the initial discharge capacity of FeOOH/GO could reach 1437.28 mAh/g. Additionally, compared to that of pure FeOOH, the reversibility of the electrochemical reaction of FeOOH/GO was improved, and the impedance value was reduced. Finally, FeOOH/GO was used directly as a lithium-ion battery (LIB) anode material to improve the kinetics of the Lithium ions insertion/extraction process and improve ionic conductivity.